Evaluation Readiness Bandung Municipality in Responding and Managing Online Public Relation with Twitter Usage - Kusumawardani, Anisa; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2014)
Abstract. Twitter inspires various parties to become main actor in chosen field. In this study, twitter is applied as an information center and also a tool of public relation. Many city information accounts have been created to realize the public service in terms of facilitating its people, build communication between related agencies and also as a tool to accommodate the aspirations of the community. In this study will be discussed about the readiness of Bandung Municipality in responding and managing twitter as a tool of online Public Relation. Online Public relation is a new thing and it is also an opportunity for the Government to improve public services. The Mayor of Bandung, Ridwan kamil asked to all Department to create a twitter account. With the presence of government agencies to the realm of social media, the public would be easier to deliver a wide range of aspirations and grievances. Social Media could make information become widen, faster, easier, and more interactive. The readiness of Bandung Municipality in managing twitter and its application needs to be evaluated. The authors did a research by doing observation and direct interviewing to five units of the SKPD (a unit Of Work Areas) that are active in responding in twitter. The research lasted for 1 month, and the author has recorded all conversation in twitter and using it as an input data & report. Author also conduct interviews to the community and the parties from each of the SKPD. Through this research with direct observations and interviews, in line with the approaches and analysis based on management function and Online Public relation, it concluded that Bandung Municipality is still not ready yet in the terms of twitter usage, as a tool of online public relation and public services improvement, both in terms of management function and also knowledge about the use of twitter and public Relation. In getting to the conclusion that this aspect of the management function, which consists of Planning, Organizing, Leading, Controlling & Staffing is the most important aspect that needs to be in the clear. Utilization of social media, especially twitter is still not effective because there are still many aspects that need to be fixed.Keywords: Twitter,Bandung, Media Sosial, Management , Public Relation